Pengaruh Kualitas Produk Wisata Umrah terhadap Minat Kunjungan Wisatawan Lansia di Annisa Travel Jakarta - Yulianandaris; Made Adhi Gunadi; Meizar Rusli (Samarinda State Polytechnic, 2020)
The interest and trend of Umrah pilgrimage combined with tourism activities continues to increase, making competition among the travel agent industry more competitive. In the Umrah tourism provider, this means very important to pay attention to the needs, wants and fulfill customer expectations by providing better product quality. This study aims to see the effect of the quality of tourism products on the main market segment in Umrah tourism which is the elderly tourists to their intention to visit and do Umrah. The research is used quantitative research methods. Data were collected from 51 respondents using questionnaire and analysis using simple linear regression analysis. The results showed that there were dimensions of the tourism product qualities that had an effect and had no effect on intention to visit. The dimensions of public facilities, human resources and accessibility are significantly influence intention to visit, whilst those classified as non-influential dimensions are the dimensions of attraction, cleanliness, information and services.